2021
DOI: 10.3390/polym13152468
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Performances of Composite Polymer Electrolytes with Porous Vinyl-Functionalized SiO2 Nanoparticles for Lithium Metal Batteries

Abstract: Composite polymer electrolytes (CPEs) incorporate the advantages of solid polymer electrolytes (SPEs) and inorganic solid electrolytes (ISEs), which have shown huge potential in the application of safe lithium-metal batteries (LMBs). Effectively avoiding the agglomeration of inorganic fillers in the polymer matrix during the organic–inorganic mixing process is very important for the properties of the composite electrolyte. Herein, a partial cross-linked PEO-based CPE was prepared by porous vinyl-functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…The ionic conductivity values are in the order of 10 −3 ~10 −4 S cm −1 . The results were comparable with the conductivity data reported in the literature, such as 5.1 × 10 −4 S cm −1 measured at 60 °C by Zhan et al [ 3 ] and 5.2 × 10 −3 S cm −1 at room temperature by Aziz et al [ 6 ]. In this study, it was experimentally observed that the ionic conductivity of the PBT–EVOH polymer composite electrolyte membrane with the 1.5% crosslinking agent ratio and 48 h immersion time could exhibit the best σ of 5.04 × 10 −3 S cm −1 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The ionic conductivity values are in the order of 10 −3 ~10 −4 S cm −1 . The results were comparable with the conductivity data reported in the literature, such as 5.1 × 10 −4 S cm −1 measured at 60 °C by Zhan et al [ 3 ] and 5.2 × 10 −3 S cm −1 at room temperature by Aziz et al [ 6 ]. In this study, it was experimentally observed that the ionic conductivity of the PBT–EVOH polymer composite electrolyte membrane with the 1.5% crosslinking agent ratio and 48 h immersion time could exhibit the best σ of 5.04 × 10 −3 S cm −1 .…”
Section: Resultssupporting
confidence: 92%
“…Damage has been reported from time to time through battery explosions of products even those produced by many renowned international companies. It has been noted that high-performance polymer composite electrolyte membranes may play important roles in battery structures, not only to provide high ionic conductivity but also to construct a thin and tough interface between anodes and cathodes [ 2 , 3 , 4 , 5 ]. Their structures and electrochemical characteristics can be crucial for energy storage and energy conversion [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhan et al [ 140 ] prepared a partial crosslinked PEO-based SPE using porous vinyl-functionalized silicon dioxide (SiO 2 ) as the filler and PEGDA as the crosslinker ( Figure 17 ).…”
Section: Polymer Composite Electrolytesmentioning
confidence: 99%
“…Various methods have been introduced to fabricate CPEs, for instance, binary salt systems [ 230 ], polymer blending [ 232 ], incorporation of additives, such as plasticiser [ 233 ], crosslinking polymer matrices [ 234 ], impregnation with ionic liquid [ 235 ], doping of nanomaterials [ 236 ], reinforcement by inorganic fillers [ 230 ], and comb-branched copolymer [ 237 ]. The characteristics of the particles used, including the particle sizes, concentration, surface area, porosity, and the interaction between particles and the polymer matrices, are crucial to determining the electronic and ionic conductivities of the CPEs [ 238 , 239 , 240 ].…”
Section: Polymer Electrolytes and The Ion Transport Modelmentioning
confidence: 99%